Annual Plan 2002-03 Planning Commission State Plan Division - Planning Commission (Planning Commission, 2002)
At the outset, the Deputy Chairman welcomed the Chief Minister of Andhra Pradesh and other Members of the State delegation. After complimenting the State for sincerely pursuing the economic and other reforms , he observed that utilization of agreed Plan outlays which was very good in the first two years of the Ninth Plan fell short of the agreed outlay in the subsequent two years, though the State expected to have performed better in the terminal year of the Ninth Plan.
Summary Records DCH/CMS 2002-03